The Effect of Leadership Style and Work Motivation on The Performance of Academic Staff - Meilana Widyaningsih; Mufti Arief Arfiansyah (Journal of Business and Management Review, 2020)
This study has purpose to analyze the effect of transactional leadership styles, transformational leadership styles, and motivation on the performance of academic staff. This study was conducted at the State Islamic Institute of Surakarta with a total sample of 30 respondents in 2020 by using simple random sampling. The results of the analysis on the variable transactional leadership style showed the value of t = 3.183 and a probability of 0.002, which means that the transactional leadership style has an effect on the performance of academic staff. Then, the results of the analysis on transformational leadership style variables showed the value of tcount = 3.418 and a probability of 0.003, which means that the transformational leadership style has an effect on performance. And the results of the analysis on the work motivation variable showed the value of tcount = 2.251 and a probability of 0.032, when compared to ttable (2.056) which means that work motivation has an effect on performance. Keywords: transformational leadership, transactional leadership, work motivation, and academic staff performance.